Kajian Visual Terhadap Poster Rewind Art Periode 2010 - 2022 - fitriani, amelia; Oetopo, Astawarin (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2023)
This study aims to analyze posters through visual communication design and the use of posters as a medium to convey information and messages. Visual arts, with inherent beauty that can be perceived through the senses, hold significant meaning in this field. Visual communication design explores creative expression and communication concepts, conveying ideas visually through graphic elements. Posters, as two-dimensional artworks, are analyzed for their effectiveness in publication, communication, and information dissemination. They serve as a means to communicate with the public, facilitating easy information delivery and acting as decorative and promotional elements The research method used is qualitative with a semiotic approach by Charles S. Pierce. The data collection technique employed is interviews with the poster designer of "Rewind Art," observations of the audience as one of the user elements providing insights into their inspiration and problem-solving approaches. The semiotic theory approach in this study examines the diversity of meanings contained in the icons, indices, and symbols of the posters.The study is centered around "Rewind Art," an annual art performance event at Jakarta State University, where posters play a crucial role in promoting and informing about the event's content. The analysis of "Rewind Art" posters focuses on typography, illustration, color, and layout to uncover elements contributing to their effectiveness. Successful posters combine simplicity, clarity, innovative ideas, and designer touches to effectively convey the intended message.